Kualitas Perencanaan Pembelajaran Mendalam Materi Membaca Teks Fiksi di SMK: Analisis Kesesuaian Dengan Kerangka Pembelajaran Mendalam - Auliyah Niswa; Suyatno Suyatno; Riki Nasrullah (Continuous Education: Journal of Science and Research, 2026)
Deep Learning is an approach developed to encourage students to build more meaningful understanding through the process of understanding, applying, and reflecting. Although various studies have examined the implementation of Deep Learning in learning practices, studies that focus on the quality of learning planning are still relatively limited. This study aims to analyze the quality of deep learning planning for fiction text reading materials in vocational schools based on its suitability with the Deep Learning framework. The study used a descriptive qualitative approach with the subjects of seven Indonesian language teachers in class X in seven SMK Negeri Kabupaten Sampang. Data were obtained through documentation and semi-structured interviews, then analyzed using thematic analysis that adapted Braun and Clarke's models. The results of the study show that all learning planning documents have contained the main components of Deep Learning which include identification, learning design, learning experience, and assessment, although the level of completeness and depth of presentation still vary. Learning planning in general has been in accordance with the learning outcomes of reading and watching Phase E, especially in developing the ability to understand, interpret, and compare information in fictional texts, but evaluative competencies related to the assessment of the quality and reliability of information have not been optimally accommodated. In addition, the principles of Deep Learning have been operationalized through learning experiences that encourage the process of understanding, applying, and reflecting as well as developing the dimensions of critical reasoning, communication, and collaboration. The research findings confirm that the quality of the implementation of Deep Learning is not only determined by the existence of planning components, but also by the depth of operationalization of each component in supporting a meaningful learning experience.